The Contribution Of The Organizational Force In The Job Empowerment Of The Student Sports Activities Management's Supervisors In Baghdad (Journal of the College of Basic Education, 2022)
The study's goal is to identify the level of organizational strength and job empowerment among the supervisors of the Department of Sports Student Activities in Baghdad, and then to identify the contributions and the impact of the organizational strength on their job empowerment. The researcher has adopted the descriptive approach by the method of correlation relations on a sample selected randomly at a rate (70%.297) of the activities sport student supervisors who are responsible for managing competitive sports Championships in the General Directorates of the six educations in Baghdad Governorate, for the academic year (2019-2020). Two measures have been adopted for each research phenomenon and making adjustments to it without affecting its goals, then bases and scientific coefficients for them have been verified to be applied on the sample amounting to (71) Supervisors from these institutions. A survey with the two scales has been conducted for the period of time from Monday 18/9/2019 until Thursday 1/12/2019 , data has been processed by using the SPSS-V26 system. The conclusions and applications have indicated that the sporting student activities management's supervisors have organizational strength and job empowerment that helps them perform important tasks in managing school competitive championships , and increasing the level of organizational strength that contributes to raising the level of job empowerment among supervisors based on managing competitive championships in Baghdad. It is necessary to pay attention to the organizational strength of the supervisors of the Department of Student Sports Activities and to support the policy of education directorates in developing them because of their effective and positive role in raising the level of their job empowerment.